2016
DOI: 10.1302/2046-3758.512.bjr-2016-0073.r1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes in osteoporosis by integrated microarray analysis

Abstract: ObjectivesIn order to screen the altered gene expression profile in peripheral blood mononuclear cells of patients with osteoporosis, we performed an integrated analysis of the online microarray studies of osteoporosis.MethodsWe searched the Gene Expression Omnibus (GEO) database for microarray studies of peripheral blood mononuclear cells in patients with osteoporosis. Subsequently, we integrated gene expression data sets from multiple microarray studies to obtain differentially expressed genes (DEGs) between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…There is contradictory data on the differentiation potential of MSCs from young and aged rats. With identifiable differences in gene expression, 22 , 23 we had hypothesized that MSCs from OVX rats would have lower osteogenic potential and would more likely differentiate to adipocytes compared with MSCs from young rats; however, this was not the case. MSCs from OVX rats had lower osteogenic differentiation potential, but they also had a lower adipogenic differentiation ability compared with MSCs from young rats.…”
Section: Discussionmentioning
confidence: 99%
“…There is contradictory data on the differentiation potential of MSCs from young and aged rats. With identifiable differences in gene expression, 22 , 23 we had hypothesized that MSCs from OVX rats would have lower osteogenic potential and would more likely differentiate to adipocytes compared with MSCs from young rats; however, this was not the case. MSCs from OVX rats had lower osteogenic differentiation potential, but they also had a lower adipogenic differentiation ability compared with MSCs from young rats.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include numerous cytokines and signalling pathways, such as nuclear receptor-interacting protein 1 (NRIP1), interleukin-1 receptor-associated kinase 3 (IRAK3), bone morphogenetic protein 7 (BMP7), SMAD family member 1 (SMAD1), MAPK3,C-X-C chemokine receptor type 4 (CXCR4), OPG/RANKL/RANKL pathway, Wnt/β-catenin pathway, cathepsin K pathway, and BMP pathway. 27 , 28 The BMP pathway is the most important signalling during these processes, as it can induce osteogenic differentiation, enhance bone formation without activating resorption and can promote bone repair without affecting non-skeletal tissues. 29 …”
Section: Ckip-1 Regulates Bone Formation Through Bone Morphogenetic Pmentioning
confidence: 99%
“…The results suggested that the differentially expressed lncRNAs were accumulated in PMOP-associated signaling pathways, including osteoclast differentiation, as well as TNF and MAPK signaling pathways. Aberrant gene expression profiles have been observed in various diseases, suggesting their potential as diagnostic biomarkers and therapeutic targets (15)(16)(17). The gene expression profiles in osteoporosis remain poorly investigated.…”
Section: Discussionmentioning
confidence: 99%